Prayer Practices of International Students at Islamic University of Indonesia: A Comparative Madhhab Study - Hidayatulloh, Muhamad Syarif; Syah, Faisal Ahmad Ferdian; Soylu, Davud (Institut Agama Islam Negeri (IAIN) Manado, 2025)
This study explores the diversity of salat (ritual prayer) practices among international students at the Islamic University of Indonesia (UII) who come from various Islamic legal madhahib (madhahib, madhahib of Islamic jurisprudence). These differing practices, particularly in salat al-farḍ (obligatory prayers), often raise questions among local students within a predominantly Syafi’i jurisprudential environment. The research aims to examine how international students perform salat and whether they adopt inclusive or exclusive attitudes in responding to local religious norms. Employing a qualitative approach grounded in Bhikhu Parekh’s theory of multiculturalism and comparative Islamic jurisprudence, this study draws on coordination with UII’s Office of International Affairs, closed and open interviews, observations, literature reviews, and Focus Group Discussions (FGDs). Data was analyzed through processes of reduction and interpretive analysis. The findings reveal significant variations in prayer practices, including the recitation of Surat al-Fatiḥah (the Opening Chapter of the Qur’an)—particularly the basmalah (the phrase “In the name of God, the Most Merciful, the Most Compassionate”)—hand positioning, the practice of qunut (a supplicatory prayer), and attitudes toward additional movements during prayer. Theoretically, this study extends comparative madhhab jurisprudence by situating lived ritual differences within a multiculturalism framework, thereby conceptualizing jurisprudential diversity not merely as a practical accommodation, but as a normative foundation for religious inclusivity in contemporary Muslim academic settings.